2000
DOI: 10.1111/j.1540-5915.2000.tb00928.x
|View full text |Cite
|
Sign up to set email alerts
|

An Evolutionary Algorithm for Sequencing Production on a Paced Assembly Line

Abstract: A new sequencing method for mixed-model assembly lines is developed and tested. This method, called the Evolutionary Production Sequencer (EPS) is designed to maximize production on an assembly line. The performance of EPS is evaluated using three measures: minimum cycle time necessary to achieve 100% completion without rework, percent of items completed without rework for a given cycle time, and sequence "smoothness." The first two of these measures are based on a simulated production system. Characteristics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…If work overload is compensated by additional workers, this amount of work is also called utility work. Papers which deal with these objectives are, for instance, Wester and Kilbridge (1964), Thomopoulos (1967), Macaskill (1973), Yano and Bolat (1989), Yano and Rachamadugu (1991), Bolat and Yano (1992b), Tsai (1995), Scholl et al (1998), Sumichrast et al (2000), Sarker and Pan (2001), Kim and Jeong (2007) and Bautista and Cano (2008).…”
Section: Literature Overviewmentioning
confidence: 99%
“…If work overload is compensated by additional workers, this amount of work is also called utility work. Papers which deal with these objectives are, for instance, Wester and Kilbridge (1964), Thomopoulos (1967), Macaskill (1973), Yano and Bolat (1989), Yano and Rachamadugu (1991), Bolat and Yano (1992b), Tsai (1995), Scholl et al (1998), Sumichrast et al (2000), Sarker and Pan (2001), Kim and Jeong (2007) and Bautista and Cano (2008).…”
Section: Literature Overviewmentioning
confidence: 99%
“…Indeed, it has been suggested that overemphasizing low-level operators and components (which is done in GAS) causes the loss of the selection of good behaviors in evolutionary processes (Fogel, 1995b). Finally, GA has been found to be less efficient as compared to ES in solving problems with many constraints (Sumichrast, Oxenrider, & Clayton, 2000).…”
Section: Evolution Strategiesmentioning
confidence: 99%
“…We ran sample experiments with different parameter settings and arrived at the chosen parameters upon the preliminary findings. This procedure is generally followed for new categories of algorithms that have not been applied in a particular context (e.g., Sumichrast et al, 2000).…”
Section: Evolution Strategy Performance For Large-scale Problemsmentioning
confidence: 99%
“…This raises the question for the real-world prerequisites under which part-oriented level scheduling is a suited surrogate model to minimize the actual model sequence-dependent costs of material supply. Preliminary computational studies on the material flows resulting from optimal sequences of part-oriented level scheduling in simulated production environments are provided by Sumichrast and Clayton (1996) as well as Sumichrast et al (2000).…”
Section: Research Needs Regarding the Relations Of Modelsmentioning
confidence: 99%